2018
DOI: 10.1038/s41598-018-25485-7
|View full text |Cite
|
Sign up to set email alerts
|

CPT1C promotes human mesenchymal stem cells survival under glucose deprivation through the modulation of autophagy

Abstract: Human mesenchymal stem cells (hMSCs) are widely used in regenerative medicine. In some applications, they must survive under low nutrient conditions engendered by avascularity. Strategies to improve hMSCs survival may be of high relevance in tissue engineering. Carnitine palmitoyltransferase 1 C (CPT1C) is a pseudoenzyme exclusively expressed in neurons and cancer cells. In the present study, we show that CPT1C is also expressed in hMSCs and protects them against glucose starvation, glycolysis inhibition, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 46 publications
1
32
0
Order By: Relevance
“…Lipid droplet biogenesis must, therefore, be essential for cell survival, but it was not clear until recently why a futile cycle of FA esterification into TAG and lipolysis would be necessary for energy production and cell survival. Studies in starved MEFs have shown that structural lipids are mobilised through autophagy of membranous organelles and that lipid droplets are necessary for at least two main reasons: (1) to prevent the lipotoxicity of FAs released by autophagy into the cytosol [ 31 ] and (2) to enable efficient transfer of FAs from lipid droplets to the network of tubulated mitochondria for oxidation [ 25 , 31 , 34 , 41 ]. The lipid droplet biogenesis in starved MEFs depends on the activation of autophagy (see discussion in Section 8.3 ) and on DGAT1 activity.…”
Section: Lipid Droplets Are Synthesized and Broken Down During Nutmentioning
confidence: 99%
See 3 more Smart Citations
“…Lipid droplet biogenesis must, therefore, be essential for cell survival, but it was not clear until recently why a futile cycle of FA esterification into TAG and lipolysis would be necessary for energy production and cell survival. Studies in starved MEFs have shown that structural lipids are mobilised through autophagy of membranous organelles and that lipid droplets are necessary for at least two main reasons: (1) to prevent the lipotoxicity of FAs released by autophagy into the cytosol [ 31 ] and (2) to enable efficient transfer of FAs from lipid droplets to the network of tubulated mitochondria for oxidation [ 25 , 31 , 34 , 41 ]. The lipid droplet biogenesis in starved MEFs depends on the activation of autophagy (see discussion in Section 8.3 ) and on DGAT1 activity.…”
Section: Lipid Droplets Are Synthesized and Broken Down During Nutmentioning
confidence: 99%
“…Since lipid droplets are central to lipid homeostasis, there are also multiple ways of crosstalk between lipid droplets and autophagy ( Figure 5 ). Autophagy may participate in lipid droplet biogenesis [ 25 , 31 , 34 , 241 , 242 ] and breakdown [ 62 ], but lipid droplets may also promote autophagy through several mechanisms [ 58 , 59 , 60 , 61 ]. Indeed, recent studies have shown that lipid droplets may be sites for autophagy initiation or provide lipids for the assembly of the autophagic machinery.…”
Section: Lipid Droplets and Autophagy/lipophagymentioning
confidence: 99%
See 2 more Smart Citations
“…This exposes TP53 or tumor protein (p53) DNA binding sites and subsequent association with RNA polymerase II ( Figure 1 ) [ 26 , 27 ]. These events enhance CPT1C and p21 expression, which play a role in cellular survival via activating autophagy and transporting long-chain fatty acids to the mitochondria, collectively enhancing β-oxidation and energy production [ 28 , 29 , 30 ]. Related to cellular survival, charged multivesicular body protein 1B (CHMP1b) is phosphorylated by AMPK, forms a “shell” around nucleosomes enriched with H3 phosphorylation and acetylation, and influences gene transcription [ 25 ].…”
Section: Histone Modificationmentioning
confidence: 99%